Western Architecture during the First Pahlavi Dynasty and Its Effects on the Lifestyle of Iranian Women - Chavardi, Javad Askari; Bigdeli, Ali; Alisoufi, Alireza; Jahanbakhsh, Heydar (Journal of History Culture and Art Research, 2017)
This study investigates the effects of modern western architecture on the culture and lifestyle of Iranian women during the first Pahlavi dynasty. For this purpose, the problem is confronted with a historical look. The widespread relationship of Iran with western countries during modern times has influenced Iranian architecture as well as other cultural areas. Thus, during this period, the traditional lifestyle and the culture of Iranian women have dramatically resembled a western style. However, this change has led to some paradoxes because of incongruency of Iranian culture and the Islamic traditions with western culture in some cases in Iran. This dissonance has become more apparent during the recent decades and criticized by many intellectuals. The changes of this period shows that some places such as Tehran University, squares, schools, streets and others are not simply a place for studying, shopping, or entertainment any more, but they are a place for public movement and protests of women and men.